Montessory Method in Training Development of Health Protocol Ambassadors Facing the Post COVID-19 Pandemic Era at SD Muhammadiyah 01 Medan - Ariga, Reni Asmara; Amelia, Rina; Astuti, Sri Budi; Fajar, Fajar Amanah Ariga; Ariga, Selviana; Ariga, Hijrah Purnama Sari; Pane, Nikmah Kemalasari (Talenta Publisher, 2022)
Along the decline COVID-19 cases in Indonesia, the implementation of Limited Face-to-face Learning (PTM) in education units was again carried out by observing the implementation of strict health protocols by education units. In the implementation, various problems were found, such as the lack of awareness of students in implementing health protocols. The solutions offered by the Community Service team to support preventing the spread of COVID-19 and improving healthy lifestyles include developing a health protocol ambassador program through a peer teaching program with the Montessori method. This activity was carried on August 8, 2022 with assistance and monitoring carried out until August 22, 2022 at SD Muhammadiyah 01 Medan with a total sample of 60 people. The results showed an increase before and after the activity, before the activity was carried out as many as 31 (51.7%) respondents were at a moderate level of knowledge, 37 (61.7%) positive attitudes and 32 (53.3%) good behavior respondents. After the activities were carried out, 47 (78.3%) respondents had high knowledge, 60 (100%) positive attitudes and 46 (76.7%) good behavior. Therefore, this method is effective in increasing the knowledge, attitudes and behavior of students' awareness about health protocols and prevention of COVID-19 transmission.